2018
DOI: 10.1093/cid/ciy454
|View full text |Cite
|
Sign up to set email alerts
|

Increased Metabolic Activity on 18F-Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography in Human Immunodeficiency Virus–Associated Immune Reconstitution Inflammatory Syndrome

Abstract: NCT02147405.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
3
25
0
1
Order By: Relevance
“…Taken together, these findings suggest ART-associated functional cellular immune recovery directed at the site of antigen may be contributing to incident lung inflammation in patients with pulmonary TB via an IRIS-like phenomenon. Also consistent with this are findings from Hammoud et al [33] that demonstrated correlations between changes in body glycolytic activity on ART and soluble inflammatory biomarkers associated with IRIS risk, including TNF-α.…”
Section: Discussionsupporting
confidence: 87%
“…Taken together, these findings suggest ART-associated functional cellular immune recovery directed at the site of antigen may be contributing to incident lung inflammation in patients with pulmonary TB via an IRIS-like phenomenon. Also consistent with this are findings from Hammoud et al [33] that demonstrated correlations between changes in body glycolytic activity on ART and soluble inflammatory biomarkers associated with IRIS risk, including TNF-α.…”
Section: Discussionsupporting
confidence: 87%
“…In totality, a global Warburg phenotype has now emerged as a classic manifestation of HIV infection. 53,64,65 Thus, the plasma metabolite signatures we observed are likely a snapshot of the global and intrinsic cellular metabolic ux that occurs during ATI in individual patients.…”
Section: Discussionmentioning
confidence: 96%
“…In a cohort of patients with multidrug-resistant TB treated with second-line TB therapy for 2 years, quantitative changes in 18 F-FDG uptake 2 months after starting treatment were associated with long-term outcomes, offering valuable early prognostic information (81). Similarly, early pathological metabolic activity on 18 F-FDG PET, before initiation of antiretroviral therapy (ART), was associated with subsequent development of HIV-related immune reconstitution inflammatory syndrome (IRIS) after initiation of ART (82).…”
Section: Clinical Translationmentioning
confidence: 99%